1978
DOI: 10.1104/pp.61.5.796
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of 2,4-Dihydroxy-7-methoxy-2H-1,4-benzoxazin-3(4H)-one in Aqueous Solutions

Abstract: Cyclic hydroxanc acids present in some species of Gramineae have been reported to be Important In resbtace of these plnts to fngi aNd insects. Since The amount of DIMBOA5 (Fig. 1) and its glucoside may total more than 1% of the dry wt of corn plants (14,16). In aqueous solutions near neutral pH, free DIMBOA has been reported to decompose quantitatively to MBOA and formic acid (28,29). This facile decomposition of DIMBOA to MBOA has been used for the measurement of DIMBOA content ofcorn by isotopic dilution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 26 publications
6
94
0
1
Order By: Relevance
“…The high persistence in soil shown by APO, much higher than its precursors, in addition to its high phytotoxicity, leads us to assign a critical role regarding chemicals defense in DIBOA producer plants, other than DIBOA or BOA, that have been proposed as the main responsibles for several plant-plant interaction phenomena (6,34,35). The occurrence of degradation in buffered aqueous solution (8,10) also enforces a careful revision of the bioassay methodologies employed in the phytotoxicity evaluation of 2,4-dihydroxybenzoxazinones and benzoxazolinones since the activities observed could be due to degradation products instead of the original materials dosed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high persistence in soil shown by APO, much higher than its precursors, in addition to its high phytotoxicity, leads us to assign a critical role regarding chemicals defense in DIBOA producer plants, other than DIBOA or BOA, that have been proposed as the main responsibles for several plant-plant interaction phenomena (6,34,35). The occurrence of degradation in buffered aqueous solution (8,10) also enforces a careful revision of the bioassay methodologies employed in the phytotoxicity evaluation of 2,4-dihydroxybenzoxazinones and benzoxazolinones since the activities observed could be due to degradation products instead of the original materials dosed.…”
Section: Resultsmentioning
confidence: 99%
“…In general terms, natural 2,4-dihydroxybenzoxazin-3-ones (DIMBOA, DIBOA) ( In addition to this bioactivity research, the low stability of DIMBOA, DIBOA, and their related benzoxazolinones in several conditions, such as biotransformation by fungi (15), and degradation in crop soil (16,17) and in aqueous solution (8)(9)(10), has been investigated. We have recently developed a complete degradation study of these allelochemicals in wheat crop soil in which we observed and characterized the conversion dynamics of these compounds into several molecules carried out by soil microbial population (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal hydroxamic acid in aqueous extracts of corn is 2,4-dihydroxy-7-methoxy-2H-l,4-benzoxazin-3(4H)-one (DIMBOA), which decomposes to 6-methoxy-2-benzoxazolinone (MBOA) in aqueous solutions (19,23). DIMBOA and MBOA ( Fig.…”
mentioning
confidence: 99%
“…Aglycone concentrations were determined using established extinction coefficients of E254 = 8500 for DIBOA and E262 = 10,000 for DIMBOA (9,26). DIBOA glucoside concentrations were determined using an extinction coefficientof E255 = 8500 (9).…”
mentioning
confidence: 99%